Namibia : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2002)
This Report on the Observance of Standards and Codes data module provides a review of Namibia's data dissemination practices against the IMF's General Data Dissemination System (GDDS), complemented by an in-depth assessment of the quality of the national accounts, consumer price index, government finance, monetary, and balance-of-payments statistics. The assessment reveals that Namibia meets the GDDS recommendations for the core comprehensive frameworks and indicators, except for the dissemination of the production index/indices, wages and earnings indicators, disaggregated data on government financing and debt, and data on public and publicly guaranteed external debt.